Electrochemical and photocurrent characterization of polymer solar cells with improved performance after GO addition to the PEDOT:PSS hole transporting layer. (April 2017) - Iwan, Agnieszka; Caballero-Briones, Felipe; Filapek, Michal; Boharewicz, Bartosz; Tazbir, Igor; Hreniak, Agnieszka; Guerrero- Contreras, Jesus
Graphical abstract: Highlights: We chemically synthesized graphene oxide (GO). BHJ solar cells with P3HT:PCBM or PTB7:PC71 BM active layers were constructed. We analyse PV properties in the level of amount of GO in PEDOT:PSS. PV and EIS depend on the polymer used, annealing temperature and amount of GO. GO in PEDOT:PSS reduce the HOMO-LUMO gap. Abstract: In this paper, chemically synthesized graphene oxide (GO) was added to modify the performance and electrochemical properties of bulk heterojunction polymer solar cells (PSCs) with different architectures. GO was obtained by modified Hummers method and fully characterized by Raman spectroscopy, Fourier Transform Infrared Spectroscopy, X-ray diffraction as well as with cyclic voltammetry (CV). Bulk heterojunction PSCs with P3HT:PC61 BM or PTB7:PC71 BM active layers and PEDOT:PSS as hole transport layers (HTL) were constructed and investigated relative to: (i) concentration of GO in HTL, (ii) acidity of GO, (iii) type of polymer used in active layer, (iv) annealing temperature of the active layer and (v) place where GO is incorporated in the devices. For PSCs, the best performance was obtained for device with the ITO/PEDOT:PSS:GO/PTB7:PC71 BM/Al architecture when the volume ratio of PEDOT:PSS to GO was 1:1. Under these conditions, a power conversion efficiency (PCE) of 5.22% with open circuit voltage Voc  = 0.654 V, short circuit current density Jsc  = 15.17 mA/cm 2, and fill factor FF = 0.53 were achieved. It is shown that for devices with P3HT:PC61 BM active layer, a better performance of device was achieved for the active layer annealed at 130 °C instead of 75 °C. For the ITO/(PEDOT:PSS):GO (1:1)/P3HT:PC61 BM (75 °C)/Al device about 75% higher PCE was found compared with reference device (PCE for device without GO = 0.64%, while PCE for device with GO = 1.07%). The influence of GO on energy gap and HOMO-LUMO levels in PEDOT:PSS was investigated by CV method. The observed effect of GO in the HTL is to reduce the HOMO-LUMO gap and to shift the LUMO position downwards in energy, with the GO contents. The devices were additionally tested by electrochemical impedance spectroscopy (EIS) and well-fitted equivalent circuits were proposed.